2014
DOI: 10.1507/endocrj.ej13-0494
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the reporting system for thyroid fine-needle aspiration cytology according to the new guidelines of the Japan Thyroid Association [Review]

Abstract: Abstract. The Japan Thyroid Association (JTA) recently published new guidelines for clinical management of thyroid nodules. This paper introduces their diagnostic system for reporting thyroid fine-needle aspiration cytology. There are two points where the new reporting system that differs from existing internationally-accepted ones. The first is the subclassification of the so-called indeterminate category, which is divided into 'follicular neoplasm' and 'others'. The second is the subclassification of follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 79 publications
2
59
0
Order By: Relevance
“…In this opinion paper, the authors introduce Asian practices for patients with thyroid nodules and describe Asian clinical practice (active surveillance for indeterminate thyroid nodules and low‐risk thyroid carcinomas), as reliable and valid means for reducing overdiagnosis and overtreatment of borderline thyroid tumours and low‐risk thyroid carcinomas . In addition, there are reports of significant variations in ROM in cytological‐histological correlation studies even when the ATA thyroid cancer management guidelines and the Bethesda system were employed .…”
Section: Introductionmentioning
confidence: 99%
“…In this opinion paper, the authors introduce Asian practices for patients with thyroid nodules and describe Asian clinical practice (active surveillance for indeterminate thyroid nodules and low‐risk thyroid carcinomas), as reliable and valid means for reducing overdiagnosis and overtreatment of borderline thyroid tumours and low‐risk thyroid carcinomas . In addition, there are reports of significant variations in ROM in cytological‐histological correlation studies even when the ATA thyroid cancer management guidelines and the Bethesda system were employed .…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of PTC is based on its histological pattern involving specific papillary architecture, yet some papillary carcinomas show not the typical histological features [2,3]. Moreover, diagnosis of thyroid cancers is initially based on the fine needle aspiration cytology of thyroid nodules [4]. However, morphology-based methods have several limitations restricting correct classification of cancer subtypes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the reporting system, CFO is included in the "Benign" classification. Currently, almost all Japanese clinicians are averse to accepting CFO as non-diagnostic [20]. Our study demonstrated that CFO and ND-other nodules differ in clinical management, in the interval before re-aspiration, and in malignancy rates.…”
Section: Discussionmentioning
confidence: 69%